328. Outcomes in Spinal Cord Injury Patients with Stage 3 and 4 Pressure Injuries at a Veterans' Affairs Hospital. (31st December 2020) - Koh, Shannon J; Van Beest, Dominique; Kargel, Jennifer; Wang, Jijia; Bedimo, Roger; Cutrell, James B; Tan, Wei-Han
Abstract: Background: Pressure injuries (PI) and the complication of PI-related osteomyelitis (PIrOM), are a significant source of morbidity and mortality in spinal cord injury (SCI) patients. This study describes the epidemiology, healthcare utilization, and outcomes of SCI patients with PI at a large Veterans' Affairs (VA) hospital. Methods: We retrospectively reviewed all SCI patients with stage 3 or 4 PI in the pelvic area admitted to the VA North Texas SCI unit from 1/1/2013 to 12/31/2018. We abstracted demographic, diagnostic testing, treatment, and outcomes data from PI-related admissions for wound care from the electronic medical record. A composite definition categorizing the diagnosis of PIrOM was created (table 1 ). Two-sample t test and Fisher's exact test were used to compare variables between flap patients (FP, those who received at least one flap surgery) and non-flap patients (NFP, those without any flap surgery). Table 1. Composite Definition for Pressure Injury-related Osteomyelitis Results: A total of 78 patients, accounting for 113 hospitalizations, and 138 unique PI, were identified (table 2 ). Patients had a mean age of 59 years at index admission and male predominance (97%). Of the 138 PI, 49% were ischial and 88% were stage 4. There were 27 FP and 51 NFP. The mean Charlson Comorbidity Index was 4.9 overall and significantly higher in the NFP vs. FP (5.2 vs. 4.3, p=0.05). Diagnostics included at least one imaging study in 76% (n=86) of hospitalizations and a bone biopsy in 45% (n=51). Bone biopsy cultures were commonly polymicrobial (47%, n=24), with anaerobes, Staphylococcus aureus, and Streptococcus species being the most predominant organisms. A diagnosis of definite, probable, or possible PIrOM was made in 14%, 16%, and 41% of hospitalizations, respectively (table 3 ). Healthcare utilization was high, with a mean length of antibiotic therapy of 54 days and mean length of stay of 122 days per hospitalization. The rates of healed PI overall at discharge and at 1 year were 27% and 39%, and 12% and 40% in the NFP group. The 1-year mortality for NFP was 22%, while all FP were alive at one year. Table 2. Demographics and Comorbidities in SCI Patients with Stage 3 and 4 Pressure Injury Table 3. Healthcare Utilization, Osteomyelitis Classification, and Outcomes in PI-related Hospitalizations Conclusion: Despite significantly high healthcare utilization, VA SCI patients with stage 3 and 4 PI had very poor wound outcomes and high mortality, particularly in NFP. Evidence-based, high value care paradigms are needed for this population and disease state. Disclosures: Roger Bedimo, MD, Gilead Sciences (Consultant)Merck & Co. (Advisor or Review Panel member)ViiV Healthcare (Advisor or Review Panel member, Research Grant or Support)